2017
DOI: 10.1371/journal.pone.0167900
|View full text |Cite
|
Sign up to set email alerts
|

A Randomized Controlled Pilot Trial of Different Mobile Messaging Interventions for Problem Drinking Compared to Weekly Drink Tracking

Abstract: IntroductionRecent evidence suggests that text messaging may help to reduce problem drinking as an extension to in-person services, but very little is known about the effectiveness of remote messaging on problem drinking as a stand-alone intervention, or how different types of messages may improve drinking outcomes in those seeking to moderate their alcohol consumption.MethodsWe conducted an exploratory, single-blind randomized controlled pilot study comparing four different types of alcohol reduction-themed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
109
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(112 citation statements)
references
References 33 publications
2
109
0
1
Order By: Relevance
“…A further review indicates that electronic‐based interventions are effective to reduce alcohol use in populations other than HNC. For example, Muench et al found that daily automated texts can help problem drinkers reduce drinking frequency and quantity significantly more than weekly self‐tracking messages. A meta‐analytic review of 28 electronic intervention trials for alcohol misuse and alcohol use disorders shows a small reduction in consumption (approximately 1 drink per week) in adults and college students at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…A further review indicates that electronic‐based interventions are effective to reduce alcohol use in populations other than HNC. For example, Muench et al found that daily automated texts can help problem drinkers reduce drinking frequency and quantity significantly more than weekly self‐tracking messages. A meta‐analytic review of 28 electronic intervention trials for alcohol misuse and alcohol use disorders shows a small reduction in consumption (approximately 1 drink per week) in adults and college students at 6 months.…”
Section: Discussionmentioning
confidence: 99%
“…There are endless subtleties in designing automated text interventions for mental health purposes. Tailoring [27] and diversifying [28] messages have shown potential for improving efficacy and reducing habituation. Sender, stimulus type, delivery medium, heterogeneity, timing of delivery, frequency, intensity, the trigger's target, structure, narrative [29], and the linguistic content of messages [30] are among the variables that need to be optimized for the purpose of the intervention.…”
Section: Related Workmentioning
confidence: 99%
“…For example, a mHealth intervention might be offered via multiple modalities, such as text message, email or calendar reminder. Like the general population [109], tailoring to the unique needs of each older adult maximizes engagement and efficacy [35].…”
Section: Providing a Context In Which Older Adults Learn And Adopt Tementioning
confidence: 99%